Investigating Explorative Character of Ozone Layer Depletion Between Pakistan and China: A Comparative Regional Study - M. Ayub Khan Yousuf Zai,; Bulbul Jan,; M. Rashid Kamal Ansari, (Journal of Basic & Applied Sciences, 2013)
In this communication we have assessed explorative nature of ozone layer dynamics using data of ozone depth from 1984-to 2010 at the stratospheric region of China and Pakistan. This study comprises the parametric evaluation that characterizes the physical behaviour of stratospheres of both the regions. For this purpose we have adopted exploratory data analysis (EDA). The results indicated an obvious distinction in the fluctuating dynamics of China and Pakistan. The models discussed in this communication can be used for public, private and government organizations and compared with other countries stratospheric ozone layer dynamics.